An Analysis of Poverty in Myanmar, Part 1 : Trends between 2004/05 and 2015 - Myanmar Ministry of Planning and Finance; World Bank Group (World Bank, Yangon, 2017)
A joint analysis of poverty and living standards was conducted by a technical team from the Ministry of Planning and Finance, Government of Myanmar, and the Poverty and Equity Global Practice of the World Bank. The findings of the joint analysis are summarized in a two-part report: Part One puts forward trends in poverty over time. Annexes include the technical details of the poverty measurement exercise. This report also makes recommendations on the need to revise the poverty measure used to reflect the needs of the population a decade after poverty was first measured in Myanmar. Part Two (forthcoming) presents the poverty profile for 2015 based on the new poverty line.